Examination of Exercise-Induced Skeletal and Cardiac Muscle Damage in Terms of Smoking - Gokhan Ipekoglu; Halil Taskın; Omer Senel (Montenegrin Sports Academy, 2019)
This study aimed to investigate the effect of acute endurance exercise on cardiac and skeletal muscles in smokers and non-smokers. Eight daily smokers (28.44 ± 3.94 years) and nine non-smokers (29.62 ± 3.46 years) were included. The subjects were not trained and performed continuous endurance exercise on a treadmill for 40 minutes at 70% of maximal heart rate. Venous blood samples were collected at baseline [preexercise (PRE)], at immediately after the exercise [post-exercise (POST)], at 2 hours after the exercise (2h), at 24 hours after the exercise (24h) to measure lactate dehydrogenase (LDH), creatine kinase(CK), creatine kinase-myocardial band (CK-MB), cardiac troponin T (TN-T), and myoglobin levels. A progressive increase was observed in all exercise-induced muscle damage parameters of the smoker and non-smoker from PRE to 2h. CK, myoglobin and T-NT levels of smokers were significantly higher than non-smokers at 24h (p=0.039, p=0.018 p=0.008, respectively). No significant difference was found between the smoking and non-smoking groups at all time points regarding CK-MB and LDH levels (p>0.05). Acute endurance exercise leads to more skeletal and myocardial damage in smokers compared to non-smokers. Smoking may increase the risk of cardiovascular events during both exercise and daily physical activity.